Analysis of organizational culture factors that influence the performance of health care professionals: A literature review - Reem lafi Almutairi; Ronal Surya Aditya; Lailatul Kodriyah; Ah. Yusuf; Fitriana Kurniasari Solikhah; Daifallah M. Al Razeeni; Siti Kotijah (AOSIS, 2022)
Hospitals in today's healthcare system are under pressure to boost their competitiveness. A number of studies have shown the disconnect between corporate culture and the enhancement of healthcare professionals' performance. While it is well accepted that an organization's culture has a substantial impact on the performance of its health care professionals in clinical practice, the mechanisms by which culture might enhance health care professionals' performance remain unclear. This paper draws on 22 literature reviews and database searches using keyword syntax from ScienceDirect, Pubmed, Google Scholar, and other relevant publications published between 2011 and 2021. Research in the field demonstrates that a company's culture may influence the efficiency and effectiveness of its healthcare employees. This overarching issue was dissected into the following themes: nurse performance mediated by discipline; the existence of cultural groups; a central focus on health care professional management; and individual, organizational, and psychological aspects. The optimal performance of nurses and the outcomes of patient care are contingent on management in the health care business knowing the cultural factors that exist in the workplace.